Retinal breaks due to intravitreal ocriplasmin - Silva, Ruwan A (Dove Medical Press, 2014)
Ocriplasmin represents a new treatment option for numerous vitreoretinopathies involving an abnormal vitreomacular interface. While the drug may circumvent the traditional risks of surgical treatment, pharmacologic vitreolysis is not devoid of risk itself. This report presents two cases, one of vitreomacular traction syndrome and the other of a full-thickness macular hole, both of which were treated with an intravitreal injection of ocriplasmin. Notably, in both cases, vitreomacular traction of the macula appears to have been alleviated; however, failure to completely relieve vitreoretinal traction from the peripheral retina generated retinal breaks with one patient eventually developing a macula-involving retinal detachment. Thus, even in instances of ‘successful’ pharmacologic treatment of vitreomacular traction, continued follow-up evaluation is essential.